2017
DOI: 10.1111/cch.12445
|View full text |Cite
|
Sign up to set email alerts
|

Fathers make a difference: positive relationships with mother and baby in relation to infant colic

Abstract: Higher levels of maternal social support during pregnancy and post partum are associated with lower rates of maternal reported infant colic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
1
12
0
3
Order By: Relevance
“…The proportion of infants with colic in this study was higher than the 5‐19% most commonly observed in other studies—25.6% in the maternal sample and 32.6% in the paternal sample—though colic rates over 25% have been reported previously . We used the same question for measuring colic in our first study and 14% of the infants in that study had colic, so it does not seem to be an issue with the phrasing of the question.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…The proportion of infants with colic in this study was higher than the 5‐19% most commonly observed in other studies—25.6% in the maternal sample and 32.6% in the paternal sample—though colic rates over 25% have been reported previously . We used the same question for measuring colic in our first study and 14% of the infants in that study had colic, so it does not seem to be an issue with the phrasing of the question.…”
Section: Discussionsupporting
confidence: 46%
“…One of the limitations of this study is that we did not have an objective measure of infant crying time (such as an audio‐recording), but relied on parental report. However, parent‐reported data on infant crying time is typically used in observational infant colic studies . Even studies that use infant crying diaries share the limitation of being inherently subjective and reliant on parents' perception of infant crying.…”
Section: Discussionmentioning
confidence: 99%
“…They were very pleased to pass on their specific needs to partners. Women mentioned the spouse as a major source of support after childbirth (25,33). In another study, some African American mothers said that they used their spouse to cope with unwanted family members' help, because they did not prefer to receive help from their relatives (34).…”
Section: Discussionmentioning
confidence: 99%
“…Незважаючи на велику кількість опублікованих досліджень, етіологія і патогенез дитячої кольки залишаються неясними і вважаються багатофакторними, що обумовлює складнощі вибору стратегії для розв'язання даної проблеми. Але завжди треба пам'ятати про те, що частина кольок -це імовірна гастроінтестинальна алергія до білка коров'ячого молока (АБКМ) (приблизно 25 % дітей із помірними або вираженими симптомами кольок як причину мають саме АБКМ [19]); частина як етіологічний фактор має дисахаридазну (лактазну) недостатність, характерну для дітей раннього віку; ще в багатьох немовлят кольки є про явом незрілості ентеральної нервової системи, яка обумовлює алодинію -сприйняття небольових стимулів як больових [20].…”
Section: частота функціональних гастроінтестинальних розладів є надзвunclassified